A novel chimeric peptide with antimicrobial activity - SARIYAR AKBULUT, BERNA (WILEY, 2015)
Beta-lactamase-mediated bacterial drug resistance exacerbates the prognosis of infectious diseases, which are sometimes treated with co-administration of beta-lactam type antibiotics and beta-lactamase inhibitors. Antimicrobial peptides are promising broad-spectrum alternatives to conventional antibiotics in this era of evolving bacterial resistance. Peptides based on the Ala46-Tyr51 beta-hairpin loop of beta-lactamase inhibitory protein (BLIP) have been previously shown to inhibit beta-lactamase. Here, our goal was to modify this peptide for improved beta-lactamase inhibition and cellular uptake. Motivated by the cell-penetrating pVEC sequence, which includes a hydrophobic stretch at its N-terminus, our approach involved the addition of LLIIL residues to the inhibitory peptide N-terminus to facilitate uptake. Activity measurements of the peptide based on the 45-53 loop of BLIP for enhanced inhibition verified that the peptide was a competitive beta-lactamase inhibitor with a K-i value of 58M. Incubation of beta-lactam-resistant cells with peptide decreased the number of viable cells, while it had no effect on beta-lactamase-free cells, indicating that this peptide had antimicrobial activity via beta-lactamase inhibition. To elucidate the molecular mechanism by which this peptide moves across the membrane, steered molecular dynamics simulations were carried out. We propose that addition of hydrophobic residues to the N-terminus of the peptide affords a promising strategy in the design of novel antimicrobial peptides not only against beta-lactamase but also for other intracellular targets. Copyright (c) 2015 European Peptide Society and John Wiley & Sons, Ltd.
Keywords: antimicrobial peptide; beta-lactamase; antibiotic resistance; delivery; cell-penetrating peptide; CELL-PENETRATING PEPTIDES; LACTAMASE-INHIBITORY PROTEIN; TEM-1 BETA-LACTAMASE; MOLECULAR-DYNAMICS; CRYSTAL-STRUCTURE; PHAGE DISPLAY; BINDING; DESIGN; ACID